The Effect of Using Fly Ash with Various Additives on the Microstructure and Compressive Strength of Self-Compacting Concrete (Review Study) (Journal of Civil Engineering Researchers, 2026)
This review article provides a comprehensive investigation into the effects of utilizing fly ash (FA) along with other mineral additives such as metakaolin (MK), silica fume (SF), hydrated lime (HL), and others on the properties of Self-Compacting Concrete (SCC). The primary objective of this study is to analyze and synthesize existing research on the simultaneous influence of various chemical additives and fly ash on the microstructure and compressive strength of self-compacting concrete. Recognized for its ease of implementation and enhanced performance, self-compacting concrete is considered an advanced technology in the concrete industry, and the use of mineral additives, particularly fly ash, can contribute to the improvement of its mechanical properties and durability.The methodology of these studies primarily involves examining the concrete microstructure using Scanning Electron Microscopy (SEM) and evaluating the compressive strength of concrete specimens at different ages. Results indicate that partial replacement of cement with activated fly ash (using sodium hydroxide) can reduce the hydration process while enhancing pozzolanic reactions, leading to improved strength properties. The optimal performance of activated fly ash-based SCC, in terms of strength, was observed at 10% to 15% replacement. SEM images revealed that fly ash particles are spherical, whereas activated fly ash particles are angular and elongated, which contributes to improved concrete matrix density and reduced porosity, thereby increasing compressive strength.Furthermore, studies on concrete containing mineral additives demonstrated that MK provides higher initial strength compared to other additives. This study concludes that the use of fly ash and other mineral additives, particularly in combination with activators or hydrated lime, can effectively enhance the mechanical and microstructural properties of self-compacting concrete, making it a sustainable and efficient option for construction applications. This review also underscores the importance of a profound understanding of the relationship between material composition, microstructure, and mechanical properties for the optimal formulation of SCC.
Keywords: Self-Compacting Concrete (SCC); Fly Ash; Compressive Strength; Mineral addition; Scanning Electron Microscopy (SEM); Interfacial Transition Zone (ITZ)